Prospective Incidence of Paediatric Inflammatory Bowel Disease in New Zealand in 2015: Results From the Paediatric Inflammatory Bowel Disease in New Zealand (PINZ) Study. Issue 5 (May 2018) - Lopez, Robert N.; Evans, Helen M.; Appleton, Laura; Bishop, Jonathan; Chin, Simon; Mouat, Stephen; Gearry, Richard B.; Day, Andrew S.
ABSTRACT: Background: The global incidence of paediatric inflammatory bowel disease (IBD) is increasing. Much of the evidence attesting to this has arisen from North America and Europe. There is a relative paucity of information on the epidemiology of paediatric IBD in the Southern Hemisphere. The present study aimed to document the prospectively collected incidence of paediatric IBD in New Zealand in 2015. Methods: All patients younger than 16 years of age and diagnosed with IBD in New Zealand between 1 January 2015 and 31 December 2015 were identified. Demographic and disease phenotypic details were collected and entered into a secure database. Age-specific population data for New Zealand were obtained and national incidence rates for IBD and its subtypes were calculated. Results: The prospectively calculated incidence of paediatric IBD, Crohn disease, ulcerative colitis (UC), and IBD unclassified in New Zealand in 2015 were 5.2 (95% confidence interval 3.9–6.8), 3.5 (2.4–4.8), 1.0 (0.5–1.8), and 0.7 (0.3–1.4) per 100, 000 children, respectively. Conclusions: Incidence rates of paediatric IBD in New Zealand are comparable to the highest rates published in the literature from Western Europe and North America. Ongoing prospective ascertainment of the incidence of paediatric IBD is required to better understand the environmental factors, which are accounting for this increase in disease burden.